HUBUNGAN KADAR GULA DARAH DENGAN KADAR UREUM DARAH PADA PENDERITA DIABETES MELITUS - Rahmi, Azzizatur (MEDIA OF MEDICAL LABORATORY SCIENCE, 2018)
Diabetes mellitus is a disease characterized by high blood sugar levels caused by interference with insulin (insulin resistance) or insulin secretion and / or both. Where blood sugar is a term that refers to the level or amount of sugar content in the blood circulation in the body. Increased levels of sugar in the blood has a direct impact on several blood vessels including blood vessels in the kidneys which is caused by the kidneys functioning to filter out the remaining metabolites and disposed of in the form of urine. If there is damage to the kidneys, the level of urea in the blood will increase. The purpose of this study was to determine the correlation between blood sugar levels and blood urea levels in people with diabetes mellitus. This research is an analytical descriptive study with a cross sectional approach using the non random accidental sampling method and primary data collection. The results obtained 23 (77%) respondents had high blood sugar levels (hyperglycemia), 7 (23%) had normal blood sugar levels (normoglycemia). Respondents with high urea levels were 21 (70%) respondents and 9 (30%) respondents had normal urea levels. Based on the results of the spearmens correlation test, a significant value of <0.005 (0.000 <0.005) is obtained which means that there is a relationship between blood sugar levels and blood urea levels in people with diabetes mellitus.